UNDERSTANDING THE SIGNIFICANCE OF MATHEMATICS IN CIVIL SOCIETY - Isa, Babangida Saidu (Sokoto Educational Review, 2018)
Mathematics is worthwhile on the account of its practical usefulness. An engineer, a scientist, a banker, a businessman, Vulcanizer, shoe-maker. cleaner, taxi-driver, farmer, industrialist or labourer needs a fair knowledge of mathematics to calculate his wage, make purchase from the market and adjust his expenditure to his income. Mathematical skills and competencies are needed beyond computational skills to enable individuals to cope with the new societal demands and to live productively in the society. Thus a fair knowledge of mathematics is essential in nearly every aspect of human life. Yet many people were not able to comprehend the benefits-of mathematics beyond the daily usage of calculating simple numbers and students ’ performance in Mathematics at various stages of the educational system is very disappointing, many people including students consider Mathematics as only a classroom discipline that has no relevance to life outside the classroom setting. It is against this background that this paper discusses the cultural, social, disciplinary, aesthetic and recreational values of mathematics in civil society. The paper therefore recommends that the society should be sensitized on other advantages of mathematics beyond the classroom setting and students at all levels should be taught the relevance of mathematics to life outside the formal classroom.